The impact of government debt on pro equality growth: Evidence from lower middle-income countries - Muhammad Kholisul Imam; Anas Tania Januari (Keynesia : International Journal of Economy and Business, 2024)
Pro equality growth is a condition of increasing economic growth with a reduction in income inequality. Data shows that in the last three decades, actual governement debt has increased. The main focus of this study is to prove whether government debt can produce pro equality growth. Moreover, there are two objectives in this study: (i) to investigate the impact of government debt on economic growth; and (ii) to investigate the impact of government debt on income inequality. This study uses panel data from 21 lower middle-income countries between 1989 and 2017. Method used in this study is three stage least squares (3sls). The estimation results show that government debt, has not been able to realize pro equality growth. Government debt can stimulate economic growth, but income inequality worsened. Although debt can be used as an investment in productive activities, the use of government debt cannot increase the accessibility and productivity of the poor. There are direct and indirect effects between government debt and income inequality. On the other hand, there is only a direct effect between government debt and economic growth, and there is no indirect effect through the income inequality pathway.